Promoting Species Knowledge: Mammal Diversity at Ragunan Zoo - A YouTube Vlog Educational Video - Adinugraha, Fajar; Purba, Dian Pirma Natasari; Dalle, Rinanda Priska; Pereira, Jefrino Reis; Lomo, Jhoni Yakobus; Kmur, Diana Insoraky Felasia; Sitinjak, Rivaldi (Borneo Journal of Biology Education (BJBE), 2024)
The lack of knowledge among students regarding animal species, particularly mammals, is a contributing factor to the loss of biodiversity. Therefore, it is essential to educate students about mammalia species through educational video. The aim of this research is to identify mammals in Ragunan Zoo for use as educational video content. The research methodology involved field exploration, followed by the creation of educational videos in the form of vlogs. Fifteen species were used as the subject of the learning videos about mammals. The species are classified into five orders: Artiodactyla (4 species), Carnivora (2 species), Primates (7 species), Proboscidea (1 species), and Rodentia (1 species). The learning videos are divided into two sections: non-primate group mammals https://youtu.be/jonAd08pNQ4  and primate group mammals https://youtu.be/iYNB9OpME4g?s. The firt video is 8 minutes and 20 seconds long and the second video is 9 minutes and 53 seconds long. These video can be use in the first step to introduce species diversity, especially mammals.